Norway : 2022 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Norway. (IMF Staff Country Reports; Country Report ;, 2022)
The economy bounced back strongly from the first wave of Covid-19 pandemic, and the recovery is well entrenched in 2022. However, risks to the outlook are considerable, given the uncertainty over spillovers from the war in Ukraine, the intensity of the pandemic globally, and in Europe, in particular, and supply bottlenecks. Given the strong fundamentals, Norway is relatively shielded and there are both upside (higher energy prices and export volumes) and downside risks (lower demand from Europe for non-energy exports). The forecast is especially sensitive to where energy prices settle, whether energy supply to Europe will be disrupted, and Norway's capacity to increase gas supplies to Europe.